Multisystem inflammatory syndrome in children (MIS-C) associated with COVID-19, clinical characteristics: A multi-center observational study from Jordan - Marwan Shalabi; Salam Ghanem; Iyad Al-Ammouri; Amirah Daher; Enas Al-zayadneh; Alaa Alsmadi; Mais Ayyoub; Samah Abughanam; Mariam Jabr; Montaha Al-Iede (Global Epidemiology)
Objective: Multisystem inflammatory syndrome of childhood (MIS-C) is a newly recognized entity associated with COVID-19 in children. The objective was to describe the clinical course for 74 patients diagnosed with this disease. Methods: A multicenter retrospective study including 5 major hospitals in Jordan was conducted. Data from children admitted with confirmed SARS-CoV-2 infection or were in close contact with confirmed cases were collected. Total of 74 patients were diagnosed with MIS-C. Clinical, laboratory, radiological and therapeutic data were collected by retrospective chart review. Results: Fever, abdominal pain, hypoxia and other manifestation occurred. Cardiac findings were less common and did not include coronary findings. Treatments were mainly Corticosteroids and IVIG. No mortality was found in this series but serious disease occurred and some patients were admitted to Pediatric Intensive Care Unit. Conclusions: This study described the epidemiology, clinical course, management, and outcome of MIS-C cases in Jordan. The findings were consistent with what has been described from other regions globally. There was a wide spectrum in the severity of presentation. Abdominal pain was more prevalent and some children were misdiagnosed as surgical acute abdomen.